What comes after profit? : A critical look at the vast potential for public higher education in the 21st century - Letizia, Angelo Letizia (Journal of Interdisciplinary Studies in Education, 2012)
The Top Jobs Act of the 21st Century (TJ21) is a state policy in Virginia which passed the legislature in June of 2011. The policy is supposed to be a blueprint of success for public higher education institutions in Virginia. Yet, this vision of progress may be simplistic and ultimately detrimental to the true progress of Virginia’s state institutions. This paper will employ a dialectal lens, borrowed from Critical Theory, to assess the view of progress expounded by TJ21. The intent is to offer a true vision of progress, a dialectal progress which entails the overcoming of contradictions inherent in a state of affairs and arriving at a new, dynamic condition which is always open to further change.